2015
DOI: 10.1007/s40262-015-0239-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Sunitinib Pharmacokinetics and Administration Time: Preclinical and Clinical Evidence

Abstract: Background and ObjectiveCircadian rhythms may influence the pharmacokinetics of drugs. This study aimed to elucidate whether the pharmacokinetics of the orally administered drug sunitinib are subject to circadian variation.MethodsWe performed studies in male FVB-mice aged 8–12 weeks, treated with single-dose sunitinib at six dosing times. Plasma and tissue samples were obtained for pharmacokinetic analysis and to monitor messenger RNA (mRNA) expression of metabolizing enzymes and drug transporters. A prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Furthermore, this chronopharmacokinetic property of sunitinib was also observed in a clinical study and was attributable to time-dependent variations in hepatic and intestinal drug transporters and metabolizing enzymes. 10 The knowledge of circadian variation in this field is accumulating and, therefore, optimization of administration time is currently considered as an important factor in determining dosing regimen in the context of chronopharmacokinetics as an approach to maximize efficacy and minimize side effect. 4 Generally, once drugs enter the body, they pass through the liver and are partially metabolized, biliary excreted, or both.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this chronopharmacokinetic property of sunitinib was also observed in a clinical study and was attributable to time-dependent variations in hepatic and intestinal drug transporters and metabolizing enzymes. 10 The knowledge of circadian variation in this field is accumulating and, therefore, optimization of administration time is currently considered as an important factor in determining dosing regimen in the context of chronopharmacokinetics as an approach to maximize efficacy and minimize side effect. 4 Generally, once drugs enter the body, they pass through the liver and are partially metabolized, biliary excreted, or both.…”
Section: Introductionmentioning
confidence: 99%
“…In total 2105 blood samples with corresponding trough samples were analyzed. Samples were taken from patients participating in nine different prospective pharmacokinetic studies (Table 1) [17][18][19][20][21][22][23][24][25]. Table 2 presents per drug pharmacokinetic parameters used, analyzed cohorts, relative differences and 90% confidence interval (90%CI) of the relative difference.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymes and transporters involved in the pharmacokinetics of drugs, such as CYP3A4 and ABCB1, have timedependent variations in expression which may have profound effect on the exposure to several drugs. Kloth & al (Kloth et al, 2015) found that sunitinib trough plasma concentrations were significantly lower when patients were administered sunitinib in the morning, than at noon or in the evening. However, AUC was not significantly different when sunitinib was administered at different time of the day.…”
Section: Time Of the Daymentioning
confidence: 92%